Technical report: determining the local stability an analysis of microcephaly induced by Zika virus (ZIKV) / Wan Nur Aliaa Wan Mohd Nor and Liyana Qadirah Ab Kadir - Wan Mohd Nor, Wan Nur Aliaa; Ab Kadir, Liyana Qadirah (2017)
A non-linear ordinary differential equation model for the risk of microcephaly induced by ZIKV was derived by using a System Dynamic Approach. This research is focusing on a group of pregnant women in Armenia (Quindio), Colombia. By solving the non-linear algebraic system, equilibrium points for each possible cause that induces microcephaly was obtained. Next, Jacobian method was used to calculate eigenvalues for each equilibrium points to estimate the local stability. Then, the local stability analysis will be use to show the behavior of each equilibrium points obtain. Finally, the result was interpreted and conclusion was made.